Findbuch der Bestände Abt. 80 und Abt. 56: Ministerium für die Herzogtümer Holstein und Lauenburg zu Kopenhagen 1852-1864 und Holsteinische Regierung zu Kopenhagen bzw. Plön 1862-1864 - Rathjen, Jörg (Veröffentlichungen des Landesarchivs Schleswig-Holstein, 2010)
The archival material documented in these finding books originates from the Ministry of the Duchies of Holstein and Lauenburg in Copenhagen and from the Holstein Government in Copenhagen and Plön in the years 1862-1864 and 1862-1864. The Ministry for the Duchies of Holstein and Lauenburg was established by the Danish King on January 27, 1852 with its seat in Copenhagen. In November 1862 the Royal Holstein Government was established, initially in Copenhagen and later in Plön. This authority was supervised and managed by the Ministry and took over most of its tasks relating to Holstein. With the political events of 1864 and the assumption of the administration of the dukedoms by the Prussian-Austrian authorities, the Ministry and the Royal Holstein Government ceased their activities.The holdings of Dept. (Abt.) 80 comprise a total of 303 running metres of archival material, while Dept. (Abt.) 56 comprises a total of 18 running metres. For reasons of the history of the authorities, section 56 of this booklet is located behind section 80 of the stock, and a common register of places, subjects and persons for both sections forms the conclusion of this booklet. For the search for a topic or a term, the subject classification should be used first and then the index as a supplement. It should be noted that the terms for the indexes come from the file titles, i. e. not all entries in the files themselves.